Dadaism as Political Installation and Language for Revolutionary Imagination: The Importance of Being Tzara and Lenin - ORLICH, Ileana Alexandra (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
The cultural fervor that ensued over the Cabaret Voltaire in Zurich 100 years ago seems quintessentially contemporary. Having entered the stage of WWI Europe with a bang, Dada and the Dadaists brought along creative interventions seen today in continuing adaptation and cultural appropriation. Using the porous dramaturgy of Tom Stoppard’s Travesties and the rich politico-cultural commentaries embedded in Andrei Codrescu’s The Posthuman Dada Guide: Tzara and Lenin Play Chess, I rely on the interaction between Dadaism and Bolshevism as an instrument of cultural analysis, with Tzara’s relational engagement tapping into our fascination with a world out of kilter.